Enhancement of nonlinear optical properties of BaTiO(3) nanoparticles by the addition of silver seeds - Yust, Brian G. (Optical Society of America, 2012)
Barium titanate (BaTiO(3)) is a technologically important material because of its nonlinear properties, such as its strong second harmonic generation and high third order susceptibility. While many nonlinear effects have been extensively studied on the bulk scale, there are still questions regarding the strength of nonlinear effects in nanoparticles. The nonlinear properties of BaTiO(3) nanoparticles and nanorods have been studied using the closed aperture z-scan technique. Silver was then grown photochemically on the surface of the BaTiO(3) nanoparticles, and it was found that the third order susceptibility increases dramatically.